A Juridical Review of The Practice of Inheritance Distribution Prior to The Division of Marital Property in East Angkola District, South Tapanuli Regency - Harahap, Adi Gunawan; Siregar, Fatahuddin Aziz; Nasution, Muhammad Arsad (Civiliza Publishing, 2025)
This paper aims to analyze the mechanism for distributing inheritance derived from marital property, identify the factors that contribute to the failure to separate such property prior to inheritance distribution, and examine this practice in light of the Compilation of Islamic Law (KHI). Marital property refers to assets acquired by a husband and wife during the course of their marriage until their separation. This study discusses the practice of dividing marital property following a death divorce (cerai mati) in Angkola Timur District, which deviates from the provisions of Article 96 paragraph (1) of the Compilation of Islamic Law. The article mandates that marital property must first be divided equally between the spouses upon the death of one party. The research employs a juridical-empirical method, utilizing primary data collected from the field and secondary data derived from Islamic legal literature and statutory regulations. The findings reveal several primary factors behind the failure to divide marital property: community customs that delay distribution until both parents have passed away, the reluctance of children to request distribution in accordance with the KHI, and situations in which the surviving husband remarries. According to the KHI, marital property must be separated prior to the distribution of inheritance. The absence of such separation results in injustice, familial conflict, and social disharmony within the community.